Synthesis and Anticonvulsant activity of New 2-(Substituted aryl/heteryl)-3-(substituted arylidenimino)-6, 8-dibromo-1,2,3,4-tetrahydroquinazolin-4(3H)-one Derivatives - Gopal, N.; Saravanan, V.S.; Jagadeeswaran, M. (Asian Journal of Chemistry, 2010)
Methyl-3,5-dibromo anthranilate was methylated from 3,5-dibromo anthranilic acid and converted to 3,5-dibromo anthranil hydrazide by reacting with hydrazine hydrate. The hydrazide was condensed with the different p- and m-substituted aromatic aldehydes in presence of alcohol and concentrated hydrochloric acid to get the 2-(substituted phenyl/heteryl)-3-(substituted arylidenimino)-6,8-dibromo-1,2,3,4-tetrahydroquinazolin- 4(3H)-one derivatives (4-14). The structures of all the synthesized compounds have been confirmed by sup 1H NMR and mass spectral data. All the synthesized compounds were screened for anticonvulsant activity by ICES test method using phenytoin as standard drug. The test compounds 5 and 14 increase seizure threshold current statistically indicating that they are highly significantly (p < 0.001) different from control group, whereas all the compounds showed moderate activity in comparison to standard drug.